MODEL PENYAJIAN UNIT GEOMORFOLOGI GUNUNG UNGARAN DAN SEKITARNYA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS BERBASIS WEB - Kusuma, Muhammad Brilliant Cahya; Aji, Ananto; Sanjoto, Tjaturahono Budi (Geo-Image, 2019)
The research is aimed to 1) know geomorphological unit in physiographic of ??Mount Ungaran and its surroundings; 2) designing a model of geomorphological unit of Mount Ungaran and its surroundings by using web-GIS. Geomorphology unit obtained through morphological and morphogenesis aspects. The analysis technique used is holistic description analysis with ideographic method. This research result in the distribution of geomorphology unit of Mount Ungaran and its surroundings namely consist of (a) Volcanic Cone of Mount Ungaran, (b) Volcanic Neck of Mount Ungaran, (c) Volcanic Foot of Mount Ungaran, (d) Volcanic Plains of Mount Ungaran, (e) Volcanic Plains of Mount Sindoro (H) anticlinal mountains, (h) anticlinal hills, (i) sinklinal valley, (j) residual form, (k) denudation volcano hill, (l) Denudation Old Ungaran Hill. (M) plateau, (n) scraped hill, (o) alluvial terraces, and (p) alluvial coastalal plain. This geomorphological units is compiled using HTML, CSS, dan QGIS with utilize qgis2web as a leaflet in order to be displayed using geographic information system based on web.